Soil physical properties, nitrogen uptake and grain quality of maize (Zea mays L.) as affected by tillage systems and nitrogen application - Wasaya, Allah; Tahir, Muhammad; Yasir, Tauqeer Ahmad; Akram, Muhammad; Farooq, Omer; Sarwar, Naeem (Italian Journal of Agronomy, 2018)
Soil compaction is a global issue pertaining to agricultural lands. The frequent use of farm machinery and field operations at the same depth are the major causes of soil compaction. The gradual increase in soil compaction deteriorates maize grain quality due to reduced nitrogen (N) uptake. Quality food production by reducing soil compaction is the need of time, which can be achieved through deep tillage and N management. In this study, three tillage systems viz. conventional tillage (using cultivator), tillage with mould board plough +2-cultivations (MBP), and tillage with chisel plough +2-cultivations (CP); and three nitrogen levels viz. 100, 150 and 200 kg ha–1 were used to evaluate their effect on soil properties, N uptake and grain quality in maize. Lower bulk density (1.41 Mg m–3), higher total porosity (0.47 m3 m–3) and higher nitrogen uptake (96.01 kg ha–1) was recorded under chisel plough (CP) compared with other tillage systems. Different N levels had significant effect on grain and total N uptake and grain quality, while soil properties remains unaffected. Higher N uptake was recorded with 200 kg ha–1 N application than other treatments. Similarly, 8.51% and 8.57% more grain protein contents were recorded with 200 kg ha–1 N during first and second year respectively. Unlike grain protein, starch and oil contents were negatively affected by N application being higher starch (71.7%) and oil contents (3.41%) with less N supply (100 kg ha–1). However, interaction effect of tillage and nitrogen levels was found non-significant for all studied parameters except for oil contents. Higher oil contents were recorded with MBP along with 100 kg ha–1 N application. Overall study indicated that deep ploughing with CP is important for maize to explore more soil area for nutrient uptake and N is also important for improving grain quality especially protein contents an important food constituent.